Quantifying the effect of PEG architecture on nanoparticle ligand availability using DNA-PAINT. Issue 24 (9th November 2021) - Andrian, Teodora; Pujals, Silvia; Albertazzi, Lorenzo
Abstract : The importance of PEG architecture on nanoparticle (NP) functionality is known but still difficult to investigate. Here, DNA-PAINT and qPAINT are used to quantify this phenomenon at a single particle and molecular level. Abstract : The importance of PEG architecture on nanoparticle (NP) functionality is known but still difficult to investigate, especially at a single particle level. Here, we apply DNA Point Accumulation for Imaging in Nanoscale Topography (DNA-PAINT), a super-resolution microscopy (SRM) technique, to study the surface functionality in poly(lactide- co -glycolide)–poly(ethylene glycol) (PLGA–PEG) NPs with different PEG structures. We demonstrated how the length of the PEG spacer can influence the accessibility of surface chemical functionality, highlighting the importance of SRM techniques to support the rational design of functionalized NPs.